Evaluating the Validity and Reliability of Questionnaires Measuring Knowledge, Attitudes, and Practices Towards Antibiotic Resistance Among Youths: A Systematic Review Protocol - Masadeh, Majd M.; Harun, Sabariah N.; Alrabadi, Nasr (Jordan Journal of Pharmaceutical Sciences, 2024)
This protocol for a systematic review describes the methodology for assessing the validity and reliability of questionnaires used in studies on antibiotic resistance among youths. It also seeks to evaluate the methodological quality of these studies in terms of their ability to influence youths’ knowledge, attitudes, and practices (KAP) regarding antibiotic resistance, as measured by the identified questionnaires. The review will include an exhaustive literature search spanning 2013 to 2023 using key databases and grey literature sources. Data from eligible studies will be extracted regarding sample characteristics, methodological quality, and questionnaire validity and reliability metrics. The participants will be categorized into secondary school, high school, and undergraduate students. The review thoroughly evaluates the instruments’ psychometric features, including face validity, internal consistency, test-retest reliability, construct validity, and hypothesis testing. Moreover, the protocol thoroughly examines the methodology and approach employed in the encompassed research, specifically emphasizing the educational setting and its impact on the efficacy of interventions to combat antibiotic resistance. The classification of individuals based on their educational stages enables a comprehensive evaluation of the effectiveness of KAP questionnaires in various educational contexts. A meta-analysis will be performed to quantify the cumulative effects of studies. The systematic review is anticipated to provide valuable insights into the validity and reliability of questionnaires used in antibiotic resistance studies focusing on youths. By evaluating the methodological quality of these studies, this review intends to contribute to the development of standardized measurement instruments and to enhance our understanding of how interventions impact youths’ KAP related to antibiotic resistance.